True height description of equatorial F-layer over Parit Raja, Batu Pahat, Malaysia - Rhazali Z.A.; Zain A.F.M. (2023)
Digisonde ionograms recorded at Parit Raja, Malaysia (Lat. 152'N, Long. 10348'E, Magnetic dip 14.3) have been used to study the variations of ionospheric F-layer true height density peak (hmax). Hourly and daily patterns of hmax as deduced from January 2005 ionograms were analysed and studied to determine the actual F-layer peak height over Malaysia. Initial observations revealed that typical height of equatorial F-layer peak was slightly higher compared to other higher latitude regions. The altitude was found to be around 55050 km during daytime and 300 km from midnight till pre-sunrise hours. 2011 IEEE.